Influence of Deformation Conditions on the Critical Damage Factor of AZ31 Magnesium Alloy - Li-juan Pang; Xin Shang; Xuefeng Zhang (Advances in Materials Science and Engineering)
The influence of deformation conditions on the critical damage factor of AZ31 magnesium alloy was analyzed in this paper. Physical experiments and numerical simulation were used to study the critical damage factor. Compression test was carried out using a Gleeble 1500 device at temperatures between 250°C and 400°C, as well as strain rates from 0.01 s−1 to 1 s−1. True stress-strain curves of samples were obtained. Based on experimental data, an Arrhenius constitutive model was constructed. Material performance parameters and constitutive model were inputted into the finite element program DEFORM. Simulation results show that the maximum damage appears on the outer edge of the upsetting drum, and damage softening behavior is more sensitive to strain rate. According to the concept of damage sensitive rate, its values were computed. The intersection of line fitted and horizontal axis was obtained in the fracture step, and its relative maximum damage value was as the critical damage factor. The distribution of the critical damage value shows that it is not a constant but fluctuates within the range of 0.1445–0.3759, and it is more sensitive to strain rate compared with temperature.